Another dimension to grazing systems : Soil carbon - Fisher, Myles J.; Santos, R.S.M. dos; Alves, Bruno J.R.; Boddey, Robert M.; Braz, S.P.; Urquiaga, S. (2007)
In 1998, Fisher et al. attempted to draw together published and anecdotal information to answer some of the questions raised by the findings of Fisher et al. (1994; 1995), that introduced pastures of African grasses on the eastern plains of Colombia accumulated large amounts of C in the soil. This review synthesises the work in both Colombia and Brazil over the last 7 years that answers some of the questions raised and speculations made by Fisher et al. (1998). The most important studies have shown that the rate at which litter decays at the soil surface has been grossly underestimated in the past. As a consequence, net aerial primary productivity (NAPP) was shown to be 33.3–33.5 t/ha/yr in well managed pastures of introduced grasses without either a legume component or N fertiliser. While data for soil C vary according to the past history and states of the pasture, well managed pastures do accumulate C in the soil to levels above that under the native grassland vegetation. Net primary productivity below ground was only slightly less than NAPP. Deficiencies of N and P are primarily responsible for the widespread degradation that occurs when introduced pastures are overgrazed and not fertilised. Heavy stocking rates profoundly change the N cycle and lead to N deficiency and hence degradation in the bulk pasture area by concentrating N recycling from faeces and urine in rest areas and watering points. Here the pasture is so damaged by trampling that it cannot take advantage of the increased fertility.